Deciphering the role of specialized ribosomes in plants´ translation efficiency - Duarte-Conde, José Antonio; Sans-Coll, Gemma; Merchante-Berg, Catharina (My University, 2023)
Translation and its regulation play an important role in plant adaptation. Ribosomes have traditionally been considered passive molecular players regarding which RNA to translate. However, this view is changing due to studies showing that specific and heterogeneous ribosomes can have an active role regulating the translation of different RNA subpools in mammals and bacteria (Genuth & Barna, 2019). In plants, the possibilities for specialization are much higher, as each ribosomal family is encoded by two to seven paralogs and there are several hints in the literature pointing towards differential paralog roles. However, whether this heterogeneity provides selective translation of specific mRNAs under particular cell conditions has yet to be demonstrated. To address this question, we are characterizing three ribosomal families, uL16 and eL18, with three paralogs each; and eL24, which has two. All paralogs are ubiquitously expressed in Arabidopsis and specific functions have been described for at least one paralog of each family. Moreover, paralogs mutant display different phenotypes as well (Falcone Ferreyra et al., 2020; Zhou et al., 2010). We will provide evidence of phenotypic variance between paralog mutants in all families under control and abiotic stress conditions. To determine if these phenotypes are due to different RNA populations being translationally affected in each mutant, we have performed RNA-seq from total and polysomal RNA from WT and mutant plants. In parallel, the different ribosomal paralogs have been tagged to determine if the translation of certain mRNAs could be paralog-dependent by performing TRAP-seq technique (Reinoso et al., 2015). We will present our progress regarding these objectives. Falcone Ferreyra et al. (2013). Plant Physiology, 163(1), 378–391; Genuth, N. R., & Barna, M. (2019). Nat Rev Genet, 19(7), 431–452; Zhou et al. (2010). BMC Plant Biology, 10, 193; Reynoso et al., (2015). Methods Mol Biol, 1284:185-207.
Keywords: Ribosomas - Congresos; Ribosomas